Efeito antinociceptivo e marcadores de estresse oxidativo do extrato enriquecido com alcaloides indólicos ativos das folhas de Tabernaemontana catharinensis - Pergher, Dáfiner (My University, 2019)
Ethnopharmacology has been important for the identification of active compounds of natural products, mainly in plants. The pain can have diverse etiologies, with complex mechanisms, being correlated with more diverse pathologies. Pharmacological activities of Tabernaemontana catharinensis (Apocynaceae) have been evidenced as: antiofidic, antimicrobial, antioxidant, antitumor, bioinseticide, anti-inflammatory and antinociceptive. The objective of this work was to evaluate the antinociceptive potential and the modulation of the oxidative stress of the enriched extract of the indole alkaloids from leaves of Tabernaemonta catharinensis (AITc) in experimental models of nociception, oxidative stress and toxicology. The AITc extract was obtained by ultrasonic extraction followed by a liquid-liquid extraction from leaves of T. catharinensis. The chemical composition of the extract was determined by high resolution mass spectrometry. For the in vivo tests, male mice (Mus musculus) Swiss were used, the extract being administered in doses of 1,0, 5,0 and 10,0 mg / kg, in the following tests: acetic acid, formalin, tail-immersion, hot plate and open field, in which saline, morphine or diazepam groups were used depending on the test to be performed. The histopathological evaluation and oxidative stress markers were performed through the collection and evaluation of organs (spleen, kidneys, liver, brain, stomach). The results of this work evidenced in the chemical characterization the presence of 10 ibolan class Ibolan alkaloids (Ibogamine, Coronaridina and Voacristina); while another three (Affinisine, Voachalotine and 12-methoxy-Nb-methylvoachalotine), alkaloids belonging to the class of Corinanians.The extract in doses ranging from 5,0 to 10,0 mg / kg, showed antinociceptive effect in the acetic acid test, inhibiting in 47.7% and 61.6% respectively. In the formalin test, a reduction in the lymph time of the legs of 47.1% (1st stage) and 43.6% (2nd stage) was observed for a dose of 5,0 mg / kg. However, the tail-immersion and hot plate tests did not express changes in the latency period, whereas in the open field test, there were no changes in locomotor activity. The oxidative damage to the lipids was higher in the stomach, and a reduction of this parameter was found in the brain. No differences in nitric oxide levels and total antioxidant status were observed in any of the tissues studied. The toxicological, biochemical and hematological tests, as well as the histopathological tests, showed no adverse effects at the administered doses. In this way, the alkaloidal extract of T. catharinensis justifies the use of this plant in the popular medicine as analgesic, probably result of a mechanism of peripheral action however more experiments will be carried out in order to elucidate the exact mechanism. This study demonstrates that the AITc extract had no toxicity, guaranteeing safe use by the population.
A etnofarmacologia tem sido importante para a identificação de compostos ativos de produtos naturais, principalmente em plantas. A dor pode ter diversas etiologias, com mecanismos complexos, estando correlacionadas com mais diversas patologias. Atividades farmacológicas de Tabernaemontana catharinensis (Apocynaceae) têm sido evidenciadas como: antiofídica, antimicrobiana, antioxidante, antitumoral, bioinseticida, antinflamatória e antinociceptiva. Desta forma, o trabalho apresentou como objetivo a avaliação do potencial antinociceptivo e a modulação do estresse oxidativo do extrato enriquecido em alcaloides indólicos proveniente de folhas de Tabernaemonta catharinensis (AITc), em modelos experimentais de nocicepção, estresse oxidativo e toxicológicos. O extrato de AITc foi obtido por extração com ultrassom seguido por uma extração líquido-líquido, a partir de folhas de T. catharinensis. A composição química do extrato foi determinada por espectrometria de massas de alta resolução. Para os testes in vivo, foram utilizados camundongos machos (Mus musculus) Swiss, sendo o extrato administrado em doses de 1,0, 5,0 e 10,0 mg/kg, nos ensaios: ácido acético, formalina, tail-immersion, placa quente e campo aberto, nos quais foram utilizados grupos controle salina, morfina ou diazepam dependendo do teste a ser realizado. A avaliação histopatológica e de marcadores de estresse oxidativo foi executada através da coleta e avaliação dos órgãos (baço, rins, fígado, cérebro, estômago). Os resultados desse trabalho evidenciaram na caracterização química a presença de 10 alcaloides indólicos da classe ibogan (Ibogamina, Coronaridina e Voacristina); enquanto outros três (Affinisine, Voachalotine e 12-metoxi-Nb-methylvoachalotine), alcaloides pertencentes à classe dos corinanianos. O extrato em doses variando de 5,0 a 10,0 mg/kg, apresentaram efeito antinociceptivo no teste de ácido acético, inibindo em 47,7% e 61,6% respectivamente. No teste de formalina, foi observada uma redução no tempo de lambedura das patas de 47,1% (1º fase) e 43,6% (2º fase) para dose de 5,0 mg/kg. No entanto, os testes tail-immersion e placa quente, não expressaram modificações no período de latência, enquanto no ensaio de campo aberto, não houve alterações na atividade locomotora. O dano oxidativo aos lipídios foi maior no estômago, e uma redução deste parâmetro foi encontrado no cérebro. Não foram observadas diferenças nos níveis de óxido nítrico e no estado antioxidante total em nenhum dos tecidos estudados. Os ensaios toxicológicos, bioquímico e o hemograma, assim como o histopatológico, não mostraram efeitos adversos nas doses administradas. Desta forma, o extrato alcaloidal de T. catharinensis justifica o uso desta planta na medicina popular como analgésico, provavelmente resultado de um mecanismo de ação periférico no entanto mais experimentos serão realizados no intuito de elucidar o mecanismo exato. Esse estudo demonstra que o extrato de AITc, não apresentou toxicidade, garantindo a utilização segura pela população.
Keywords: Plantas medicinais; Etnofarmacologia; Tabernaemontana; Alcalóides indólicos; Medical plants; Ethnopharmacology; Tabernaemontana; Indole alkaloids